Relationship of Renal Function Tests and Electrolyte Levels with Severity of Dehydration in Acute Diarrhea - Gauchan, E; Malla, K K (Journal of Nepal Health Research Council, 2015)
Background: Acute diarrheal illness constitutes a major cause of morbidity and mortality in children in developing countries. Most of the complications of diarrhea occur due to excessive fluid and electrolyte loss; adverse complications are seen more with increasing severity of dehydration. This study was conducted to identify the relation of renal function and electrolyte abnormalities in children with varying severity of dehydration. Methods: This study was carried out in Manipal Teaching Hospital, Pokhara, Nepal over duration of one year. The aims were to find out the association of renal function and electrolyte disturbances with type of diarrhea, severity of dehydration and their relation to outcome. All children more than one month and less than 15 years with acute diarrhea were included in the study. Data were entered and analyzed by SPSS version 19. Statistical analysis applied was Chi-square test. A p-value of <0.05 was taken as significant. Results:Â Acute watery diarrhea was the commonest type of diarrhea in children. Dehydration was associated more with Acute Watery Diarrhea than with Invasive Diarrhea. Renal function and electrolyte abnormalities were seen more in Acute Watery Diarrhea with increasing levels of blood urea, serum creatinine and abnormal levels of serum sodium seen with increased severity of dehydration. Conclusions: Abnormalities in renal function and electrolytes correlated significantly with severity of dehydration. The outcome of patients correlated with severity of dehydration with mortality occurring in 18.1% of patients with Severe dehydration, 0.8% of Some dehydration with no mortality in the No dehydration group. Keywords: Acute diarrhea; children; dehydration; electrolytes; renal function.